Evolving foodscapes: Tracing trajectories of urban and peri-urban food sharing initiatives for just food transitions - Davies, Anna; Cho, Hyunji (My University, 2025)
Urban and peri-urban (UPU) area food systems need reconfiguration to support just transitions towards sustainability. Collaborative acts around food – food sharing for brevity – have been mooted as a potentially productive arena for enacting such a transition, with research exploring the location, goals, and activities of individual food sharing initiatives (FSIs) internationally. Situated conceptually at the intersection of diverse economies approaches and critical mapping, with an overarching concern for achieving just transitions to sustainable food systems, this paper advances understanding of FSIs by adopting a novel longitudinal lens and focusing on the UPU scale. Implementing a co-designed and collaboratively translated system for identifying and categorizing FSIs that have a digital presence in two European cities: Milan and Barcelona, we contextualize and compare the results uncovered, contrasting these with findings from earlier research to establish evolutionary trajectories for urban FSI landscapes. The expanded mapping process offers significant empirical insights tracing the often invisible but dynamically evolving location, form, and function of UPU FSI landscapes. These methodological and empirical insights are interrogated to identify what contribution critical mapping of FSIs at the UPU scale makes to allied efforts for just and sustainable food systems. In conclusion, while the approach outlined has limitations in terms of resource intensity and explanatory power, we see the approach as one vital component in furthering comprehensive understanding of UPU food systems, providing opportunities to: document diverse food geographies; create new spatial imaginaries; support efforts for greater food democracy, and advocate for more equitable distribution of sustainable food sharing initiatives.
PUBLISHED
https://doi.org/10.1016/j.geoforum.2025.104318
Keywords: Food; Urban; Sharing; Critical mapping; Counter Mapping; Translation; Diverse economies; Smart & Sustainable Planet